The health and educational costs of preterm birth to 18 years of age in Australia - Newnham, JP; Schilling, C; Petrou, S; Morris, JM; Wallace, EM; Brown, K; Edwards, L; Skubisz, MM; White, SW; Rynne, B; Arrese, CA; Doherty, DA (Wiley, 2021)
Background Preterm birth is the greatest cause of death up to five years of age and an important contributor to lifelong disability. There is increasing evidence that a meaningful proportion of early births may be prevented, but widespread introduction of effective preventive strategies will require financial support.